Respuesta :

Answer:

The answer is 3.

[tex]\longrightarrow{\purple{3}}[/tex] 

[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}[/tex]

[tex] \frac{(6a + b)(a + b) - 7b(a + b)}{2 {a}^{2} - 2 {b}^{2} } [/tex]

[tex] \\= \frac{(a + b)(6a + b - 7b)}{2( {a}^{2} - {b}^{2}) } [/tex]

[tex] \\= \frac{(a + b)(6a + b - 7b)}{2(a + b)(a - b)} [/tex]

[tex] \\= \frac{6a - 6b}{2(a - b)} [/tex]

[tex] \\= \frac{6(a - b)}{2(a - b)} [/tex]

[tex] \\= 3[/tex]

( OR )

[tex] \frac{(6a + b)(a + b) - 7b(a + b)}{2 {a}^{2} - 2 {b}^{2} } [/tex]

[tex] \\= \frac{6 {a}^{2} + 6ab + ab + {b}^{2} - 7ab - 7 {b}^{2} }{2( {a}^{2} - {b}^{2} )} [/tex]

[tex] \\= \frac{6 {a}^{2} - 6 {b}^{2} + 7ab - 7ab }{2( {a}^{2} - {b}^{2} )} [/tex]

[tex] \\= \frac{6 {a}^{2} - 6 {b}^{2} }{2( {a}^{2} - {b}^{2} )} [/tex]

[tex] \\= \frac{6( {a}^{2} - {b}^{2} )}{2( {a}^{2} - {b}^{2} )} [/tex]

[tex] \\= \frac{6}{2} [/tex]

[tex] \\= 3[/tex]

Note:

[tex] {a}^{2} - {b}^{2} = (a + b)(a - b)[/tex]

[tex]\huge{\textbf{\textsf{{\orange{My}}{\blue{st}}{\pink{iq}}{\purple{ue}}{\red{35}}{\green{♬}}}}}[/tex]

ACCESS MORE